Girls in power : gender, body, and menstruation in adolescence - Fingerson, Laura, 1974- (State University of New York Press, 2006)
"Girls in Power offers a look at the social aspects of menstruation in the lives of adolescent girls - and also in the lives of adolescent boys. The book extends our theoretical and analytical understanding of youth, gender, power, and embodiment by providing a more balanced view of adolescent social life."--Jacket.
Keywords: Teenage girls -- Psychology.; Menstruation -- Social aspects.; Human body -- Social aspects.; Sex role.; Adolescentes -- Psychologie.; Menstruation -- Aspect social.; Corps humain -- Aspect social.; Rôle selon le sexe.; sex role.; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence.; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers.; Human body -- Social aspects; Menstruation -- Social aspects; Sex role; Teenage girls -- Psychology